1
$\begingroup$

This question is for an intro class in probability theory :)

Let $$A, B, C$$ be three events that are pairwise & jointly independent. Show that $$A^c$$ and $$B \cup C^c$$ are also independent.

I started with some definitions. Pairwise & joint independence give us the following: $$P(A \cap B) = P(A)P(B)$$ $$P(B \cap C) = P(B)P(C)$$ $$P(A \cap C) = P(A)P(C)$$ $$P(A \cap B \cap C) = P(A)P(B)P(C)$$

I could also show that pairwise independence of the complements of the events holds, ie. $$P(A^c \cap B^c) = P(A^c)P(B^c)$$ $$P(B^c \cap C^c) = P(B^c)P(C^c)$$ $$P(A^c \cap C^c) = P(A^c)P(C^c)$$

The way I'm thinking about this problem is to simply follow the definition of independence. Show that: $$P(A^c \cap (B \cup C^c)) = P(A^c) \cdot P(B \cup C^c) = P(A^c) \cdot (P(B) + P(C^c) - P(B \cap C^c))$$ And the work I've done so far: $$P(A^c \cap (B \cup C^c)) = P((A^c \cap B) \cup (A^c \cap C^c)) = P(A^c \cap B) + P(A^c \cap C^c) - P((A^c \cap B) \cap (A^c \cap C^c) = P(A^c \cap B) + P(A^c \cap C^c) - P((A^c \cap (B \cap C^c)) = P(A^c)P(B) + P(A^c)P(C^c) - P(A^c \cap (B \cap C^c))$$ This is where I get stuck. I think this method reduces the problem to proving $$A^c, (B \cap C^c)$$ are independent, which I can't seem to do. Any hints?

$\endgroup$
1
$\begingroup$

$P(A^{c} \cap (B\cap C^{c}))=P (B\cap C^{c}))-P(A \cap (B\cap C^{c}))$. Now $P (B\cap C^{c}))=P(B)-P(B\cap C)=P(B)-P(B)P(C)$. Also $P(A \cap (B\cap C^{c}))=P(A\cap B) -P(A\cap B \cap C)=P(A)P(B)-P(A)P(B)P(C)$. Now just put all these together to get independence of $A^{c}$ and $B\cap C^{c}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.